Towards a ‘just’ conservation psychology - Klarmann, Stephanie E.; Barnes, Brendon R. (PINS-Psychology in Society, 2022)
Climate change and biodiversity loss are serious concerns for environmental researchers and conservationists. However, the impact of climate change and biodiversity loss disproportionately affects low-income communities, indigenous groups, and people of colour. Conservation initiatives, however, sometimes perpetuate historical injustices of marginalised people. We argue that environmental justice may be effectively merged with conservation psychology to promote a just conservation psychology. We discuss a case study of a South African community impacted by conservation-related environmental injustices under apartheid. We discuss the role of capacity building in a community-based conservation initiative that promotes justice, human wellbeing, and conservation goals.